Case Based Oral Mucosal Diseases (Springer Singapore, 2018)
This book includes real-time photographical recording and panoramic summary of 105 cases with oral mucosal diseases along with their diagnosis and management. This book reflects the characteristic clinical manifestations through images of each case presented. In addition to the medical history, examination, diagnosis, pathology and management of each case, a comprehensive commentary is introduced in the end of each chapter with an emphasis on the normative clinical train of thoughts and guidelines.